Comunicación visual y posicionamiento de marca: claves en la visualización de los emprendimientos rurales - Almao Malvacias, Valeria Alejandra; Suárez Alvarado, Julia Yvette; Alvarado Chávez, Troi Ernesto (Scripta Mundi, 2023)
In this research, there were examined the effects of the interventions in COMIDPROL entrepreneurships developed by Graphic Design students from the University of Guayaquil, focusing specifically on the visual communication strategies implemented. The main objective of this study was to evaluate the visual communication effectiveness on digital platforms and the impact on the brand positioning of those organizations. To achieve this, an exploratory and descriptive research approach was implemented, complemented by a non-experimental and cross-temporal design. In the research, qualitative techniques such as interviews, observation guides, bibliographic and documentary analysis were presented, along with a survey as a quantitative technique. The main findings demonstrated that the visual elements generated through the Fondo Competitivo de Investigacion (FCI) project have had a beneficial impact on the brand positioning of these organizations. However, areas of potential improvement were identified in terms of the consistency and quality of visual communication on their digital platforms. Consequently, a basic guide was presented as a proposal, guide which allows these organizations to keep their social networks updated, exposing visual elements that contribute to the positioning of their brands.